Prehospital Evaluation of the FAST-ED as a Secondary Stroke Screen to Identify Large Vessel Occlusion Strokes. (4th May 2022) - Dowbiggin, Patricia L.; Infinger, Allison E.; Purick, Gabrielle T.; Swanson, Douglas R.; Asimos, Andrew; Rhoten, Jeremy B.; VonCannon, Shellie; Dometrovich, Melissa; Studnek, Jonathan R.
Abstract: Introduction: The Field Assessment Stroke Triage for Emergency Destination (FAST-ED) was developed to identify Large Vessel Occlusion Strokes (LVOS) presenting out of hospital, although there is limited prospective research validating its use in this setting. This study evaluated the test characteristics of the FAST-ED to identify LVOS when used as a secondary stroke screen in the prehospital environment. Secondary analysis compared the performance of the CPSS and the FAST-ED in identifying an LVOS. Methods: This prospective, observational study was conducted from April 2018 to December 2019 in a municipal EMS system with all ALS ambulance response. The FAST-ED was implemented as a secondary screening tool for emergent stroke patients who had at least one positive Cincinnati Prehospital Stroke Screen (CPSS) item. CPSS and FAST-ED scores were extracted from prehospital electronic care reports, while the presence of LVOS was extracted from hospital records. Results: A total 1, 359 patients were enrolled; 55.3% female, 47.5% white, with a mean age of 69.4 (SD 15.8). In this cohort, 11.3% of patients experienced an LVOS. The mean FAST-ED for a patient experiencing an LVOS was 5.33 (95%CI 4.97–5.69) compared to 3.06 (95%CI 2.95–3.12) ( p  < 0.001). A score of greater or equal to 4 yielded the highest combination of sensitivity (77.78%) and specificity (65.34%) with positive likelihood ratio 2.24 (95% CI 2.00–2.52) and negative likelihood ratio 0.34 (95% CI 0.25–0.46). Area under the ROC curve was 0.77 (95%CI 0.73, 0.81). A CPSS with all three items positive demonstrated a sensitivity of 73.20% and 69.57% specificity, with an ROC area of 0.73 (95% CI 0.70–0.77). When comparing a FAST-ED ≥4 to a CPSS of all positive items, there was no significant difference in sensitivity ( p  > 0.05), and the FAST-ED had a significantly lower specificity than the CPSS ( p  < 0.005). Conclusion: As stroke care advances, EMS agencies must consider their destination triage needs. This study suggests agencies must consider the use of single versus secondary scales, and to determine the ideal sensitivity and specificity for their system.